Perceptions of sport injuries of young elite swimmers - Lehtinen, Mari (2012)
Mari Lehtinen, 2012. Perceptions of sport injuries of young elite swimmers. Department of Sport Sciences. University of Jyväskylä. Master’s Thesis of Sport and Exercise Psychology. 64 pages.